Acute Toxicity Test of Tamarillo Fruit Ethanol Extract (Solanum betaceum Cav.) on the Levels of Liver Transaminase Enzymes in Male Wistar Rats - Ary Nahdiyani Amalia; Rini Dwi Yulianti; Eko Hidayaturrohman Khumaeni; Denok Tri Hardiningsih (Medical and Health Journal, 2026)
Indonesians traditionally utilize tamarillo for its various health benefits. However, the lipophilic compounds it contains have the potential to cause hepatotoxicity and increase transaminase enzymes, namely SGPT and SGOT enzymes. The study aimed to test the toxicity of tamarillo ethanol extract acutely on SGPT and SGOT levels in male Wistar white rats. The study used a post-test only experimental design with a control group design. Fifteen rats were randomly divided into five treatment groups. Group K1 as a control was given distilled water, group K2 was given paracetamol 2.5 g/kgBW, while groups K3, K4, and K5 were each given tamarillo ethanol extract in single doses of 200, 400, and 600 mg/kgBW. After 24 hours, rat blood serum samples were taken through the orbital sinus to measure SGPT and SGOT levels using the UV test method. The results showed that the average SGPT levels increased in the K2 group by 295.34±13.31 U/L and K5 by 93.67±19.03 U/L. Meanwhile, the average SGOT levels increased in the K2 group by 874±25.06 U/L, K4 by 164.67±7.57 U/L and K5 by 213.34±13.50 U/L. The One-Way ANOVA test showed a significance value of p=0.000 in the K2 and K5 groups for SGPT, while SGOT in the K2, K4 and K5 groups. Administration of tamarillo ethanol extract can cause liver damage at doses of 400 mg/kgBW and 600 mg/kgBW.